On Nonhomogeneous Second Order Difference Inclusions of Accretive Type in Banach Spaces. (11th June 2018) - Jamshidnezhad, Parisa; Saeidi, Shahram
ABSTRACT: In this paper, we investigate the existence, uniqueness and asymptotic behavior of solutions to a nonhomogeneous second order difference inclusion of accretive type in Banach spaces. We develop new methods and significantly extend and improve some known results in the literature. Our conclusions are new even for Hilbert spaces.